???????? ???????? ?? ??? ??? ?? ?????? ?????? (EL-ESÂLIBU'L-BELAĞIYYE FI KISSATI NUH F'IL-KUR'ANI'L-KERIM) - KAKL, ARUMIA AGID (Fırat Üniveristesi, 2019)
Bu çalışma Kur'ân-ı Kerim'deki Nuuh (a.s) kıssasında yer alan belagat üsluplarının çağunu ele almaktadır. Bu çalışmada îcaz, itnâb, kasr, fasıl, vasıl gibi meanî üslupları, teşbih ve mecaz gibi beyan üslupları, lafzi ve manevi güzelleştirici sanatlar olarak bedi' üslupları işlenmiştir. Bu çalışmanın en önemli hedefi bu kıssanın içindeki belagat sırlarını ve sanatlarını açığa çıkarmak ve bu kıssada kalbe etki eden mucizevi estetik tasvirleri göstermektir. Anahtar Kelimeler: Arapça, Belagat, Kur'ân, Kıssa, Nuh (a.s)

This study dealt with many rhetorical methods which are included in the story of Noah, peace be upon him, in the Holy Qur'an. This includes: Semantic methods and forms such as brevity, redundancy, short forms, separation and interfacing ; statement methods such as analogy and metaphor; methods of language euphemism of phonetic and semantic improvements. The most important objective of the thesis is to highlight the artistic and hidden rhetorical aspects of the story and shows the kind of miraculous metaphors and analogies being used along with their outstanding impact on the readers. Keywords: Arabic, rhetoric, Qur'an, story, Noah
Kur'ân-ı Kerim'de Nuh suresinde Belağat üslupları (The rhetorical methods in the story of Noah in the Holy Quran)
Keywords: Din; Dilbilim; Doğu Dilleri ve Edebiyatı